PENGOPTIMALISASIAN KEBERSIHAN LINGKUNGAN DALAM MENINGKATKAN KESADARAN KESEHATAN MASYARAKAT KAMPUNG BABAKAN DESA CISONDARI - Ikhsan Hambali; Gufron Abadan Maksum; Agung Prayoga; Jajat Darmansyah (Politeknik STIA LAN Bandung, 2023)
The problem of environmental health is one of the social problems in life that has not been resolved until now. Individual awareness of cleanliness is a very influential factor on environmental health that impacts community groups. Therefore, providing understanding to the public about the importance of keeping the environment clean, especially in household waste management, must be increased. The author uses the PAR (Participatory Action Research) method in solving environmental problems. Based on observations by residents of Kampung Babakan who have a background in agriculture and animal husbandry. Therefore, in improving environmental hygiene, the community is given theory and action in managing household waste, namely by sorting organic and inorganic waste, then utilizing waste that can still be used, and disposing of waste that is not useful for final disposal.